The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Structural and diagenetic controls on flow pathways in fractured Triassic Muschelkalk and Keuper limestones, southern Germany – Implications for geoenergy exploration - Jasemin Ayse Ölmez; Benjamin Busch; Christoph Hilgers (Journal of Structural Geology, 2026)

Reservoir quality controls in the Lower Buntsandstein and their relation to detrital grain size, URG, SW-Germany - Benjamin Busch; Lennart L. Böke; Christina Schmidt; Matthias Warnecke; Christoph Hilgers (Geothermics, 2025)

Petrophysical Characterization of Metamorphic Rocks using X-ray Micro-CT data – Implications for fluid flow - Ritwik Chakraborty; Michael Späth; Akash Kumar; Benjamin Busch; Britta Nestler; Manish A. Mamtani; Christoph Hilgers (Journal of Structural Geology, 2025)

Understanding the interplay of depositional rock types, mineralogy, and diagenesis on reservoir properties of the coal-bearing Langsettian and Duckmantian strata (Bashkirian, Pennsylvanian) of the Ruhr Area, NW Germany - Jonas Greve; Benjamin Busch; Dennis Quandt; Mathias Knaak; Christoph Hilgers (International Journal of Earth Sciences, 2024)

Reservoir quality of Upper Cretaceous limestones (Ahlen-Fm., Beckum Member, Münsterland Cretaceous Basin): effects of cementation and compaction on the compactable depositional volume - Jasemin Ayse Ölmez; Benjamin Busch; Christoph Hilgers (International Journal of Earth Sciences, 2024)
The Upper Cretaceous limestones unconformably overlie Upper Carboniferous coal-bearing lithologies and are studied to assess their effect on rising mine-water levels in the Ruhr mining district. Upper Cretaceous sedimentary rocks from the Münsterland Cretaceous Basin have previously been studied regarding their sedimentary structures and fossil content. However, understanding the petrophysical and petrographic heterogeneity in regard to sedimentary properties and their effect on fluid migration pathways is yet missing. Utilizing He-pycnometry, Klinkenberg-corrected air permeabilities, p-wave velocities, transmitted and reflected light analyses, point-counting and cathodoluminescence, we assess the petrophysical, geomechanical and mineralogical properties. Porosity ranges from 1.0 to 18.7% and permeability ranges from < 0.0001 to 0.2 mD, while p-wave velocity ranges between 2089 and 5843 m/s. Mechanical compaction leads to grain rearrangement, deformation of calcispheres, foraminifera and ductile clay mineral laminae. Above and below clay laminae, compaction bands of deformed calcispheres develop. Early diagenetic mineral precipitation of ferroan calcite in inter- and intragranular pores reduces porosity and permeability and influences geomechanical properties. An underestimated aspect of limestone petrography is the relationship of the original primary compactable depositional volume and the influence of compaction, deformation and cementation during early and late diagenesis on reservoir properties. The detrital dominated limestones show an originally high compactable depositional volume (CDV). Overall, reservoir qualities are poor and indicate the sealing potential of the studied lithologies. The Upper Cretaceous (Campanian) limestones thus may act as a barrier for increasing mine-water levels from dismantled, post-mining subsurface hard coal mines in the region. Graphical abstract

Rock characteristics and reservoir properties of Upper Carboniferous (Stephanian A–B) tight siliciclastic rocks from the Saar–Nahe basin (SW Germany) - Dennis Quandt; Benjamin Busch; Jonas Greve; Christoph Hilgers (International Journal of Earth Sciences, 2024)
The environmental consequences of mine flooding in the Saar hard coal district, post-mining re-use concepts in the course of the energy transition, and the potential of coalbed methane production require an understanding of subsurface rock properties on the microscale. In this study, mineralogy, microtexture, microstructure, porosity, permeability, and geochemistry of an Upper Carboniferous (Stephanian A–B) drill core recovered in the Saar–Nahe basin are quantified. Based on these data, the diagenetic history and reservoir quality are analyzed regarding mine flooding and coalbed methane potential. The feldspar-poor and igneous rock fragment-free siliciclastic rock succession shows multiple fining upward sequences deposited in a fluvial environment during the pre-volcanic syn-rift phase of the Variscan intramontane Saar–Nahe basin. Intercalated small-scale coarsening upward sequences are related to the floodplain where near-surface soft-sediment deformation and paleosol formation took place. Porosity (< 7%) of the tight siliciclastic rocks is mainly controlled by an interplay of authigenic microporous kaolinite, dissolution porosity, and quartz cement, whereas permeability (< 0.05 mD) shows no systematic variation with petrography. During burial, quartz cements preserved porosity by stabilizing the granular framework against mechanical compaction, while phyllosilicates were ductilely deformed reducing reservoir quality. Relative phyllosilicates and quartz contents and mean grain size are reliably inferred from SiO 2 /Al 2 O 3 ratios (1.8–28.8), Ba (0.0108–0.0653 wt%), Rb (0.0024–0.0181 wt%), and Sr (0.0013–0.0086 wt%) concentrations measured with a portable x-ray fluorescence analyzer. Regarding coalbed methane production and mine flooding, sealing of cleats and heterogeneous subsurface rock properties due to dynamically changing depositional settings during the Late Carboniferous need to be considered. Graphical abstract

Post-mining related reactivation potential of faults hosted in tight reservoir rocks around flooded coal mines, eastern Ruhr Basin, Germany - Felix Allgaier; Thomas Niederhuber; Benjamin Busch; Birgit Müller; Christoph Hilgers (Geomechanics for Energy and the Environment, 2024)

Evolution of Upper Carboniferous tight sandstone reservoirs in the Ruhr and Lower Saxony basins (NW Germany) of the Central European Variscan foreland - Dennis Quandt; Benjamin Busch; Christoph Hilgers (Marine and Petroleum Geology, 2024)

Characterization of pore space in Permo-Triassic sandstone from SW-Germany using the anisotropy of magnetic susceptibility - Agnes Kontny; Benjamin Busch; Julius Schenk; Ilnar Khasanov (International Journal of Earth Sciences, 2023)
Pore space in siliciclastic rocks is one of the most important petrophysical properties in geothermal and hydrocarbon reservoir rock characterization. We used the anisotropy of magnetic susceptibility (AMS) of ferrofluid-impregnated Permo-Triassic sandstones of different Buntsandstein and Rotliegend facies as a proxy for pore space anisotropy and preferred flow direction as a case study for reservoir characterization. We compared the calculated ferrofluid porosity (2–21%) with He porosity (2–26%) and permeability (0.002–214 mD) and described the sediment microstructure using petrographic point-counting analysis. For water- and oil-based ferrofluid impregnation, we observed a positive correlation with He porosity and mass and susceptibility impregnation efficiency were used to control the quality of the impregnation process. Triaxial to oblate magnetic rock fabrics were mostly mimicked by the magnetic pore fabrics, except for some of the water-based ferrofluid impregnated samples, where magnetic ellipsoid shapes changed from oblate to prolate. AMS of the unimpregnated sandstones reflects well defined primary sedimentary to diagenetic fabrics with grain imbrication and cross bedding along with more laminated sedimentary structures. Deviation in ferrofluid-impregnated AMS axes orientation can be related either to the low anisotropy < 1.07 in sandstones from the Lower and Upper Buntsandstein, or the low impregnation efficiency. The mimicry is mostly better when the magnetic susceptibility of the sandstone is higher due to a higher concentration of phyllosilicates while micro-porosity is controlled by the clay fabric. A comparison of sediment petrography with magnetic pore fabrics suggests that the pore space is controlled by the bedding of the sandstones with mostly no preferred flow direction within the bedding plane. Graphical Abstract

Fault leakage and reservoir charging in the Upper Rhine Graben, Germany – Assessment of the Leopoldshafen fault bend - Felix Allgaier; Benjamin Busch; Christoph Hilgers (Marine and Petroleum Geology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Compaction control on diagenesis and reservoir quality development in red bed sandstones: a case study of Permian Rotliegend sandstones - Alexander C. Monsees; Benjamin Busch; Christoph Hilgers (International Journal of Earth Sciences, 2021)
Authigenic minerals formed during diagenesis in conjunction with compaction by burial have long been known to lead to porosity-loss of sandstones, and a subsequent deterioration in reservoir quality. The diagenetic impact on reservoir quality and permeability heterogeneity measured horizontal and vertical to bedding was characterized in three fluvio-eolian Lower Permian Rotliegend outcrops from the Flechtingen High, the northern Hesse Basin (both Germany) and the Vale of Eden (UK) using point-counting, polarized light-microscopy, helium pycnometry and permeability measurements. Results show significant porosity (10 to 35%) and permeability (0.01 to 10,000 mD) ranges largely independent of depositional environment. The major control on reservoir quality in Cornberg Sandstones are dolomite and siderite cementation in conjunction with illitization and illite and kaolinite cementation, leading together with quartz cementation to a mostly cemented IGV and poorest reservoir quality (avg. horizontal permeability: 0.96 mD). Flechtingen Sandstones are most intensely compacted due to the lack of significant early diagenetic cement phases and continuous illitic grain-to-grain coatings, which inhibited intense quartz cementation but enhanced chemical compaction at quartz grain contacts, resulting in intermediate reservoir quality (avg. horizontal permeability: 34.9 mD). Penrith Sandstones lack significant authigenic phases besides quartz due to carbonate dissolution during uplift. They show the least amount of detrital feldspars and clay minerals, leading to no major reservoir quality reduction by burial diagenetic clay mineral alterations, resulting in the highest reservoir quality (avg. horizontal permeability: 5900 mD). Additional results highlight higher horizontal to vertical permeability ratios k h / k v in less homogeneous sandstones of < 10 mD of 10, and in more homogenous, higher permeable sandstones > 1000 mD of 1. Although detrital and authigenic sample compositions vary throughout the studied areas, the general effect of grain coatings coverages on syntaxial cement inhibition and chemical compaction can be delineated. This study increases the understanding of porosity reduction in sandstones, as it confirms the necessity to differentiate between the illitic grain-to-grain coatings and illitic grain-to-IGV coatings. As a result, the enhancing effect of illite on chemical compaction on quartz grain-grain boundaries can be better constrained, as well as the effect of grain coatings on quartz cementation. This is relevant for reservoir quality and risk assessment in hydrocarbon and geothermal plays as well as in storage.

Quantification of Biomass Production Potentials from Trees Outside Forests—A Case Study from Central Germany - Dominik Seidel; Gerald Busch; Benjamin Krause; Claudia Bade; Carola Fessel; Christoph Kleinn (BioEnergy Research, 2015)

Interaktive Visualisierungen zur Unterstützung von Biodiversitätsforschung und -management in einem Entwicklungsland — Erfahrungen und Herausforderungen - Gertrud Schaab; Benjamin Asser; Kerstin Busch; Patrick Dammann; Nirmal Ojha; Hannes Zimmer (KN - Journal of Cartography and Geographic Information, 2009)